2013
DOI: 10.1002/pola.26724
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the mechanism of 1,3‐dienes cationic polymerization. II. Structure of poly(1,3‐pentadiene) synthesized with tBuCl/TiCl4 initiating system

Abstract: The microstructure of poly(1,3‐pentadiene) synthesized by cationic polymerization of 1,3‐pentadiene with tBuCl/TiCl4 initiating system is analyzed using one‐dimensional‐ and two‐dimensional‐NMR spectroscopy. It is shown that unsaturated part of chain contains only homo and mixed dyads with trans−1,4‐, trans−1,2‐, and cis−1,2‐structures with regular and inverse (head‐to‐head or tail‐to‐tail) enchainment, whereas cis−1,4‐ and 3,4‐units are totally absent. The new quantitative method for the calculation of conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…This allows us to conclude that the initially formed macromolecules D , due to the high reactivity of terminal conjugated double bonds, interact/copolymerize with the growing chains B with the formation of branched chains E with a trifunctional branch point and a substituted allyl cation as a terminal group (reaction IV, Scheme ). The presence of such vinyl groups in the poly(1,3‐pentadiene) was confirmed by NMR spectroscopy . Moreover, it was shown that these olefinic groups are not fragments of the 3,4‐units of the poly(1,3‐pentadiene) due to the absence of the signal of methyl carbon atom of thr 3,4‐unit in the 13 C NMR spectrum .…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…This allows us to conclude that the initially formed macromolecules D , due to the high reactivity of terminal conjugated double bonds, interact/copolymerize with the growing chains B with the formation of branched chains E with a trifunctional branch point and a substituted allyl cation as a terminal group (reaction IV, Scheme ). The presence of such vinyl groups in the poly(1,3‐pentadiene) was confirmed by NMR spectroscopy . Moreover, it was shown that these olefinic groups are not fragments of the 3,4‐units of the poly(1,3‐pentadiene) due to the absence of the signal of methyl carbon atom of thr 3,4‐unit in the 13 C NMR spectrum .…”
Section: Resultsmentioning
confidence: 83%
“…At low t BuCl/TiCl 4 ratio, room temperature, or under monomer‐starved conditions, however, chain branching becomes significant (Table ). Note, a terminal chlorine‐end group is formed only after “inverse” trans‐ 4,1 monomer addition to the growing chain (reaction III in Scheme ) . It should be also noted here that chain transfer to a counterion leading to chains containing tert ‐butyl head and terminal chlorine groups (i.e., giving structure similar to C ) and the regeneration of Lewis acid cannot be fully excluded.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations